The Application of Rubber Seed as Activated Carbon for Removal Methylene Blue by Using Microwave - Ema Luvita Sari; M. Faizal; Tuti Indah Sari (Program Pascasarjana Universitas Sriwijaya, 2020)
Activated carbon prepared from rubber (Havea brasiliensis) seeds was used to remove methylene blue from aqueous solutions. Adsorption studies were conducted to evaluate the effect of contact time and amount of carbon active on the removal of methylene blue at temperature of 25oC. The equilibrium adsorption data of methylene blue on activated carbon were analyzed by Freundlich and Langmuir isotherm model. This research compare between conventional heating and microwave heating, various of mass adsorben and various of radiation time. Carbon was activated by using various KOH using Conventional and Microwave Heating . The best adsorption was shown in Impregnation Ratio 1:1,5 carbon and KOH which dried using microwave heating.It was 3,486 mg/g was qe value. The percentgae of adsorption was 69,72%. The best result of adsorption MB using various of mass adsorben was shown in 0,4 gr. The absorption kinetic models were predicted by pseudo-first-order and pseudo-second-order. The pseudo-second-order kinetic and pseudo second order model was fitting equilibrium adsorption data. The results of adsorption methylene blue on aqueous solutions shown that rubber seeds as carbon active can be used as material for adsorption.